Bus Robberies in Belo Horizonte, Brazil: solutions for Safe Travel - Oliveira, Elenice De Souza (Crime & delinquency, 2023)
This study examines the spatial patterns and other situational determinants leading to the high number of bus robberies in Belo Horizonte. Main research questions include patterns of robberies, spatial concentration, locations prone to robberies, and environmental characteristics therein. This study also provides a variety of safety measures based on the Situational Crime Prevention approach. The Rapid Assessment Methodology (RAM) was employed using both quantitative and qualitative data. It involves spatial analysis, direct observation of hot spots using a safety audit protocol, and focus group discussions with key participants. Bus robberies involve minimum risk and low detection and arrest. The ?hottest products? to be stolen include electronic devices and cash. The robberies occur at specific times and locations depending on opportunity. As many crimes go unreported, police data have inaccuracies. Therefore, it is impossible to verify the exact location of the robberies. This study concludes that for safe travel preventive measure should focus on reducing crime opportunities. A collaborative effort is needed from agencies and individuals alike. Further research should focus on examining why the majority of bus robberies are concentrated in only two main bus routes. Are these hot spots just recent spikes or are they chronic?